2003
DOI: 10.1016/s0886-3350(03)00334-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between aberrations to improve or reduce visual performance

Abstract: For low levels of aberration, the RMS wavefront error is not a good predictor of visual acuity. Clinically, it is important to define how aberrations interact to optimize visual performance. New metrics of optical/neural performance that correlate better with clinical measures of visual performance need to be adopted or developed, as well as new clinically viable measures of visual performance that are sensitive to subtle changes in optical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
249
1
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(278 citation statements)
references
References 19 publications
11
249
1
13
Order By: Relevance
“…Although the grading system has a 0 score, the mean density is 9.3% and the maximum density is 25.5%. 21,22 reported that aberrations located in the central and upper areas of the Zernike pyramid tend to cause greater visual quality distortion. We included the internal HOAs because the crystalline lens is responsible for the increase in ocular aberrations that occurs with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Although the grading system has a 0 score, the mean density is 9.3% and the maximum density is 25.5%. 21,22 reported that aberrations located in the central and upper areas of the Zernike pyramid tend to cause greater visual quality distortion. We included the internal HOAs because the crystalline lens is responsible for the increase in ocular aberrations that occurs with aging.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates aberration interactions among Zernike terms as reported by Applegate and colleagues. 6 Both in the laboratory by using adaptive optics 3 and in clinical studies, aspheric IOLs have been shown to reduce ocular SAs, improve contrast sensitivity, and improve night driving performance. 2,4 However, 2 recent studies 13,14 reported no differences between aspheric and spherical IOLs in low-contrast visual acuity, high-contrast visual acuity, and contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…5 Applegate and colleagues 6 have reported that aberrations in different Zernike terms interact to increase or decrease optical performance. It is unclear what the optimal amount of SA would be in eyes with various HOAs.…”
Section: Introductionmentioning
confidence: 99%
“…[70][71][72][73][74][75] It would be expected that, at any pupil diameter, lower levels of HOAs are associated with better distance visual performance, although it is known that similar levels of root-mean-square (RMS) wavefront aberrations distributed between different Zernike coefficients do not necessarily imply equal performance. 76,77 Several studies evaluated the optical performance after hybrid multifocal IOL implantation. Souza and colleagues, 27 Rocha and co-workers 45 and Ortiz and associates 78 studied the optical performance of the AcrySof ReSTOR IOL and compared it with a monofocal IOL.…”
Section: Wavefront Aberrationsmentioning
confidence: 99%